Teaching competencies of physical education teachers in primary education (comparative study between accredited and non-accredited schools) - Ahmed Eıd; Khaled Awad (Türk Spor ve Egzersiz Dergisi)
This study aims at comparing the level of teaching competencies of physical education teachers in both Primary Education phases in accordance with (gender, educational level, quality of educational accreditation), using descriptive survey method.The study sample included 160 male and female physical education teachers from the accredited and non-accredited schools in primary education in Port said, Ismailia, Suez, and Sharkia governorates. They have been randomly chosen, and divided into basic sample involving 120 male and female teachers and exploratory sample involving 40 teachers. The most important results is There are statistically significant differences between accredited and non-accredited schools in the level of teaching competencies of physical education teachers in favor of physical education teachers in the accredited.